INVESTIGATING EFL UNIVERSITY STUDENTS’ MOTIVATION IN LEARNING - Abdalla, Rezhan (Al-Adab Journal, 2023)
It is believed that, motivation can affect all aspects of life. As it is self-evident in the literature, motivation has an enormous impact on teaching and learning EFL. The aim of this paper is to find out whether the students are motivated to learn EFL or not, and what type of motivation do they have; whether it is instrumental motivation or integrative motivation? This study has been conducted in the context of Kurdish EFL students at the University of Halabja, English Language Department. The problem this study is trying to tackle is to find the important role that motivation plays in learning the English language, and whether there is a lack of motivation from the EFL students, and then find ways to improve them. To conduct this study, the quantitative approach was followed, and a Likert-Scale questionnaire was designed, and was distributed among 50 EFL male and female students. The results indicated that EFL learners at the College of Basic Education in the English Language Department at University of Halabja are, to a great extent, motivated in EFL learning. Moreover, the results also presented the majority of the students have instrumental motivation rather than integrative motivation. Based on the results, some recommendations for University EFL lecturers are being presented in order to build upon the type of motivation that students already have to have the best teaching outcome.